Self-stigma dan kualitas hidup orang dengan psoriasis: Menilik peranan self-compassion sebagai moderator: Self-stigma and quality of life for people with psoriasis: Examining the role of self-compassion as a moderator - Wijaya, Grazella Natasha; Hidayat, Lidia Laksana (Persona:Jurnal Psikologi Indonesia, 2022)
Abstract Psoriasis is a skin-based autoimmune disease. Individuals creating self-stigma often internalize stigma about skin disease. Self-stigma was found to reduce the quality of life of psoriatic individuals. Self-compassion is thought to weaken the impact of self-stigma on quality of life. However, this has yet to be studied within the psoriatic. This study aims to determine and understand the role of self-compassion as a moderator of the effect of self-stigma on the quality of life of psoriatic individuals. An explanatory mixed-method study was conducted. Quantitatively, through purposive sampling, 167 individuals aged 18-65 years diagnosed with psoriasis for at least two years were involved. Instruments used were Psoriasis Internalized Stigma Scale, Self-Compassion Scale, and Dermatology Life Quality Index, processed through Hayes Macro PROCESS moderating analysis technique. Qualitatively, data were obtained through interviews with two participants and analyzed thematically. Results showed that self-compassion could not be a significant moderator, and several factors were considered more influential. Future study needs to consider personality factors. Although self-compassion could not significantly moderate, its effect on self-stigma could still be considered for intervention. Keywords: Psoriasis; self-compassion; self-stigma; quality of life Abstrak Psoriasis adalah penyakit autoimun yang menyerang kulit. Stigma yang beredar terkait penyakit kulit kerap diinternalisasi menjadi self-stigma dan ditemukan mengurangi tingkat kualitas hidup individu psoriasis. Self-compassion diduga dapat melemahkan dampak dari self-stigma terhadap kualitas hidup. Namun hal ini belum pernah diteliti pada kelompok psoriasis. Penelitian ini bertujuan untuk mengetahui dan memahami peran self-compassion sebagai moderator antara pengaruh self-stigma terhadap kualitas hidup individu psoriasis. Metode penelitian yang digunakan adalah mixed-method eksplanatori. Secara kuantitatif, melalui purposive sampling, penelitian melibatkan 167 individu berusia 18-65 tahun yang telah didiagnosis psoriasis selama setidaknya dua tahun. Instrumen yang digunakan adalah Psoriasis Internalized Stigma Scale(a=0,92), Self-Compassion Scale(a=0,87), dan Dermatology Life Quality Index(a=0,99), diolah menggunakan teknik analisis moderasi Macro PROCESS Hayes. Data kualitatif didapatkan melalui wawancara terhadap dua partisipan dan diolah dengan teknik analisis tematik. Hasil penelitian menunjukkan bahwa self-compassion tidak dapat berperan sebagai moderator yang signifikan. Hasil wawancara menemukan beberapa faktor yang diduga lebih berpengaruh dalam melemahkan pengaruh self-stigma terhadap kualitas hidup. Penelitian selanjutnya perlu mempertimbangkan faktor kepribadian individu. Meskipun tidak secara signifikan memoderasi, self-compassion dinilai potensial untuk membantu permasalahan self-stigma sehingga dapat dipertimbangkan dalam intervensi. Kata kunci: Kualitas hidup; psoriasis; stigma diri; welas diri